Rescuing zinc anode–electrolyte interface: mechanisms, theoretical simulations and in situ characterizations - Liu, Zhenjie; Zhang, Xiaofeng; Liu, Zhiming; Jiang, Yue; Wu, Dianlun; Huang, Yang; Hu, Zhe (Chemical science (Cambridge), 2024)
The research interest in aqueous zinc-ion batteries (AZIBs) has been surging due to the advantages of safety, abundance, and high electrochemical performance. However, some technique issues, such as dendrites, hydrogen evolution reaction, and corrosion, severely prohibit the development of AZIBs in practical utilizations. The underlying mechanisms regarding electrochemical performance deterioration and structure degradation are too complex to understand, especially when it comes to zinc metal anode–electrolyte interface. Recently, theoretical simulations and in situ characterizations have played a crucial role in AZIBs and are exploited to guide the research on electrolyte engineering and solid electrolyte interphase. Herein, we present a comprehensive review of the current state of the fundamental mechanisms involved in the zinc plating/stripping process and underscore the importance of theoretical simulations and in situ characterizations in mechanism research. Finally, we summarize the challenges and opportunities for AZIBs in practical applications, especially as a stationary energy storage and conversion device in a smart grid.